Commentary: Dealing with the Aftermath. (16th September 2016) - Agid, Yves
Abstract : In 2006, our team reported our experience in the use of bilateral high-frequency stimulation of the subthalamic nucleus (STN) in patients with severe levodopa-responsive forms of Parkinson's disease (PD). 1 The aim was to better understand and manage the difficulties experienced by patients who undergo neurosurgery, and by their families.